White Zombie as Captivity Narrative and the Death of Certainty - Anderson, Mark C (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
Horror films such as White Zombie (1932) reveal viewers to themselves by narrating in the currency of audience anxiety. Such movies evoke fright because they recapitulate fear and trauma that audiences have already internalized or continue to experience, even if they are not aware of it. White Zombie’s particular tack conjures up an updated captivity narrative wherein a virginal white damsel is abducted by a savage other. The shell of the captivity story is as old as America and relates closely to the Western and to the frontier myth, from which the Western emerged. What inexorably links the Western and all zombie films is the notion of containment. Whereas the Western sought to contain the American Other, all zombie films ask, instead, what happens if the other breaks through the proverbial gates. In other words, what if containment fails?